TATANAN KEHIDUPAN BARU PADA AKOMODASI DAN RESTORAN PARIWISATA - Ni Made Rai Kristina; I Gusti Ketut Indra Pranata Darma (UHN IGB Sugriwa Denpasar, 2021)
The hospitality industri is one part of the world of tourism which plays an important role wherever located. The role of the hospitality industri is not only as a place to stop and rest, but it is a beginning of the economic activities of other industries. The arrival of covid-19 virus in early 2020, no doubt hit all the industrial sectors in the world including the hospitality industri. For almost 3 months, people in the world are forced to live in fear of the covid-9 virus. The World Health Organization (WHO) also called for new life order as a new form of adaptation for all people in the world to this virus until a cure is found.Based on the presence of the virus, the hotel industri has welcomed new life by following strict rules in force following local government recommendations. This research will try to find out the form of the new life protocol accommodation at bali which get significant impact. The method using direct study and literature. So hopefullye get the right steps to be applied to other regions by following the prevailing customs in the area.